Dinamika Keterkaitan Keluarga dan Problematika Pengasuhan Anak Usia 7 Tahun - Husna, Kania; Nurafni, Nurafni; Mufiedi, Muhammad (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
Abstract: The family is the smallest social group in society which consists of father, mother and children. Which means that everything is interconnected in terms of building a harmonious family. And children are human beings who continuously grow and develop over time in every process of their growth and development towards being fully human. Thus, children become the main focus in a family, especially parents, to be cared for and educated well, with the aim of giving birth to children who are healthy, achievers and have noble character. Apart from all that, the journey in caring for children is not always smooth. Especially when a child reaches the age of 7 years, at that time the child's cognitive, social and emotional development reaches the most important level and a time when everything develops rapidly. So, it is not uncommon to find several problems that are present in this process and that parents have to face. Thus, based on this background, the author feels it is important to carry out this research, which it is hoped will be useful for developments in the world of education. In order to obtain research data that is in accordance with what happens in the field and expect the existing data to be as detailed as possible. So the type of research method we use is qualitative with a case study approach using interview, observation and documentation methods. The results of this research show that the family is an element that is interconnected with each other. And in the process of raising a 7 year old child, there are several problems faced by parents. Where each family has its own way of solving existing problems. Keywords: 7 Year Old Child, Family, Problem. Abstrak: Keluarga merupakan kelompok sosial terkecil dalam masyarakat yang mana terdiri dari ayah, ibu dan anak, Semuanya saling memiliki keterkaitan dalam hal membina keluarga yang harmonis. Kemudian anak merupakan insan yang terus-menerus bertumbuh dan berkembang seiring berjalannya waktu dalam setiap proses tumbuh kembangnya menuju manusia seutuhnya. Sehingga, anak menjadi fokus utama dalam sebuah keluarga khususnya orang tua untuk diasuh dan dididik dengan baik, dengan tujuan melahirkan anak yang sehat, berprestasi juga berakhlak mulia. Telepas dari semua itu, perjalanan dalam pengasuhan kepada anak tidaklah selalu mulus. Terutama ketika anak mencapai usia 7 tahun, dimana pada masa itu perkembangan kognitif, sosial dan emosional anak mencapai pada taraf yang paling penting dan masa dimana semuanya berkembang dengan pesat. Sehingga, tak jarang ditemukan beberapa masalah yang hadir dalam proses tersebut dan harus dihadapi oleh orang tua. Dengan demikian, atas latar belakang tersebut penulis merasa penting untuk melakukan penelitian ini, yang nantinya diharapkan dapat bermanfaat bagi perkembangan dalam dunia pendidikan. Agar didapatkan data penelitian yang sesuai dengan yang terjadi dilapangan serta mengharapkan data yang ada serinci mungkin. Maka jenis metode penelitian yang kami gunakan adalah kualitatif dengan pendekatan studi kasus menggunakan metode wawancara, observasi serta dokumentasi. Hasil penelitian ini menunjukkan bahwa keluarga merupakan unsur yang saling berkaitan satu sama dengan yang lain. Dan pada proses pengasuhan anak usia 7 tahun terdapat beberapa masalah yang dihadapi para orang tua. Dimana tiap-tiap keluarga memiliki caranya masing-masing dalam menyelesaikan masalah yang ada. Kata Kunci: Anak 7 Tahun, Keluarga, Masalah.